Challenges and prospects in cropping intensification and agricultural mechanization for improved food production in Bangladesh river deltas - International Rice Research Institute (International Rice Research Institute, 2022)
The video presents multiple benefits of pursuing cropping diversification and intensification in farmers' fields facing climate risks and threats. It also highlights the potential of agricultural mechanization to improve farm production systems further improving the livelihood of marginalized farmers in the coastal zones of Bangladesh. Livelihood options for women's participation in entrepreneurial activities are also presented and advocated by the Initiative on Asian Mega Deltas (AMD).